Ensuring of Haemostasis in Patients With Postextractional Dental Hemorrhages - Oleg Zanoaga; Valentin Topalo; Dumitru Sirbu (Romanian Society of Oral Rehabilitation, 2011)
This work has focused on assessing the efficacy of the local haemostatic treatment through application of sutures in 42 patients with postextractional dental hemorrhage caused by local factors, arterial hypertension, thrombocytopenia and oral anticoagulant medication. According to the obtained data, application of sutures in patients with postextractional dental hemorrhages occurring due to thrombocytopenia and oral anticoagulant medication is associated with a considerable increase of the rate of hemorrhage recurrences. At the same time it has been established that application of sutures has a positive influence on the results of treatment in patients with hemorrhages caused by arterial hypertension and local factors. Consequently, the doctor will choose the proper method of treatment relying on the anamnesis or clinical data which will direct him toward the etiological factor which has been involved in the occurrence of hemorrhage. This work has focused on assessing the efficacy of the local haemostatic treatment through application of sutures in 42 patients with postextractional dental hemorrhage caused by local factors, arterial hypertension, thrombocytopenia and oral anticoagulant medication. According to the obtained data, application of sutures in patients with postextractional dental hemorrhages occurring due to thrombocytopenia and oral anticoagulant medication is associated with a considerable increase of the rate of hemorrhage recurrences. At the same time it has been established that application of sutures has a positive influence on the results of treatment in patients with hemorrhages caused by arterial hypertension and local factors. Consequently, the doctor will choose the proper method of treatment relying on the anamnesis or clinical data which will direct him toward the etiological factor which has been involved in the occurrence of hemorrhage.